Affinity labeling of the catalytic subunit of cyclic AMP-dependent protein kinase by N alpha-tosyl-L-lysine chloromethyl ketone. - Kupfer, A (1979)
The catalytic subunit of cyclic AMP-dependent protein kinase (from rabbit skeletal muscle; ATP:protein phosphotransferase, EC 2.7.1.37) was found to be irreversibly inactivated by chloromethyl ketone derivatives of lysine and phenylalanine, chemical reagents originally designed for labeling the active sites of the proteolytic enzymes trypsin and chymotrypsin. This inactivation was shown to occur at pH 7.5 and 22 degrees C, conditions under which chemically related alkylating reagents such as chloroacetamide and chloroacetic acid (which do not possess the amino acid side chain) fail to inactivate the enzyme. In the case of the chloromethyl ketone derivative of N alpha-tosyl-L-lysine, the enzyme could be protected by its nucleotide substrate (MgATP), by one of its protein substrates (histone H2b), and by its regulatory subunit which, upon binding, shields the active site of the catalytic subunit. Differential labeling experiments, together with kinetic studies of the rates of modification of the sulfhydryl groups in the enzyme before and after inactivation with the chloromethyl ketone, suggest that the loss of activity is associated with one (kinetically characterized) sulfhydryl group present either at the active site of the enzyme or at a site intimately associated with it. The general implications of these results regarding the interpretation of affinity labeling experiments carried out in complex mixtures of proteins or under in vivo conditions are discussed.